Unbalanced Multiple-Description Video Coding with Rate-Distortion Optimization - Singh Raghavendra; Ortega Antonio; Comas David; Marqués Ferran (EURASIP Journal on Advances in Signal Processing, 2003)
We propose to use multiple-description coding (MDC) to protect video information against packet losses and delay, while also ensuring that it can be decoded using a standard decoder. Video data are encoded into a high-resolution stream using a standard compliant encoder. In addition, a low-resolution stream is generated by duplicating the relevant information (motion vectors, headers and some of the DCT coefficient) from the high-resolution stream while the remaining coefficients are set to zero. Both streams are independently decodable by a standard decoder. However, only in case of losses in the high resolution description, the corresponding information from the low resolution stream is decoded, else the received high resolution description is decoded. The main contribution of this paper is an optimization algorithm which, given the loss ratio, allocates bits to both descriptions and selects the right number of coefficients to duplicate in the low-resolution stream so as to minimize the expected distortion at the decoder end.